A learnability study on Wordwall.net: Online educational tool for mathematics learning - Yanuarto, Wanda Nugroho; Setyaningsih, Eka (Al-Jabar: Jurnal Pendidikan Matematika, 2024)
Background: Schools were compelled to switch to distance learning due to community quarantine measures and lockdowns imposed during the global health crisis. In this context, Wordwall.net emerged as a valuable platform, enabling users to independently create interactive games, thereby supporting the remote learning process.Aim: The purpose of this study is to demonstrate how online teaching tools such as Wordwall.net can help teachers enable interactive learning when used correctly.Method: This study employs a cross-sectional analysis to evaluate the effectiveness, efficiency, and user satisfaction of utilizing Wordwall.net as a learning medium for Basic Integration material. This approach encompasses both classroom and online learning, with a particular focus on trigonometry as the final topic mandated by the curriculum. A total of 268 randomly selected volunteer students participated in this research.Result: Using Wordwall.net as a teaching resource for fundamental integration meets the needs of all students, regardless of their background. Furthermore, the findings provide insight into the instructional material's usability in terms of efficiency, efficacy, and satisfaction.Conclusion: Wordwall.net was effective in teaching the essential integration lesson. Therefore Wordwall.net allows teachers to create interactive games and printed classroom resources.